Potensi Sifat Ekspansif Tanah Kelempungan - M. Suherman (Jurnal Jalan-Jembatan, 2005)
During the reconnaissance and preliminary stage of a project, identification of expansif clay soils is essential to allow for appropriate sampling, testing and design stages. The inve stigation must actually comprise two important phases. The first is recognition and identification of the soil as expansive soil and the second is for design prediction. The common identification methods are based on standard classification result, such as grain size analysis and Atterberg limits, however other tests used in identifying potentially swelling soils are also available.